Tetracationic porphyrin derivatives against human breast cancer - Gamelas, Sara R. D. (2021)
Photodynamic therapy (PDT) is an approved therapeutic approach and an alternative to conventional chemotherapy for the treatment of several types of cancer with the advantages of reducing the side effects and developing resistance mechanisms. Here, was evaluated the photosensitization capabilities of 5,10,15,20-tetrakis[4-(pyridinium-1-yl-methyl)phenyl]porphyrin (3), its N-confused isomer (4) and of the neutral precursors (1) and (2) and the results were compared with the ones obtained with the cationic 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin (TMPyP). Both regular porphyrin derivatives 1 and 3 showed higher efficiency to generate singlet oxygen than TMPyP. The PDT assays towards MCF-7 cells under red light irradiation (λ > 640 nm, 23.7 mW cm-2) demonstrated that the cationic porphyrin 3 is an efficient photosensitizer to kill MCF-7 breast cancer cells. The study of the cell death mechanisms induced by the photodynamic process showed that the studied porphyrin 3 and TMPyP caused cell death by autophagic flux and necrosis.